Biological methods for the assessment degree pollution of water objects by hydrobionts faunistic structure - Blyalova, Zh.Zh.; Abukenova, V.S. (Fundamental and Experimental Biology, 2017)
The article provides information about the effectiveness of biological methods of determining the degree of saprobity of water bodies in species composition of aquatic organisms that inhabit aquatic ecosystems data. The species composition of the reservoir depends on many natural factors: the magnitude of the soil particles, the flow velocity of water, temperature, amount of dissolved oxygen. Fast flowing water contains more oxygen than slow current or standing. That's why in rivers with strong currents, inhabit oxygen-demanding inver-tebrates. The more pollution, the more changes its species composition. Result in characterization of the different biological methods of assessing water pollution. Also this article are consider of the advantages and disadvantages of these methods. Noted that the method Pantla-Bukk modification Sladecek is a convenient method when saprobiological analysis. Saprobiological analysis being the most important element in the control of pollution of surface waters and bottom sediments, allows you to: to assess the quality of surface waters and bottom sediments as habitat the organisms inhabiting the ponds and watercourses; to determine the aggregate effect of the combined effects of pollutants; set the direction and the change of water biocenoses in terms of environmental pollution; to determine the ecological status of water bodies and ecological consequences of contamination.